Obtaining and Studying Technology of Dry Substance Silver Nanoparticles Obtained by “Green Synthesis” Method Using Scutellaria Iscandaria L. - Iroda B. Shermatova1, Mokhigul G. Ismailova2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Silver nanoparticles were synthesized by the method of “Green Synthesis” using extracts of ScutellariaIscandaria L. The “Green” pathway for the synthesis of silver nanoparticles has been described using anaqueous extract of the plant Common Skullcap as a reducing and stabilizing agent. A dry powder of silvernanoparticles was obtained from the Synthesized Suspension. The role of Luteolin flavonoid contained inScutellaria Iscandaria L. extract in the synthesis of silver nanoparticles as a reducing and stabilizing agentis shown, the possible mechanism of nanoparticle formation is given. The synthesized silver nanoparticleshave been studied by infrared spectroscopy, mass spectroscopy (ICP-MS), and high-performance liquidchromatography (HPLC). The size and shape of the obtained nanoparticles were characterized by the AtomicForce Microscopy (AFM) method. The antimicrobial activity of dry powder and aqueous suspension withsilver nanoparticles was also studied at the Strains Test: St.aureusATCC 25923, B.subtilis ATCC 6633,Candida alb. 885-653.